The Relationship between Perceptions and Attitudes Towards the Covid-19 Pandemic and Perceptions of Aging and Old Age among Academics Aged 65 and Above - Gülbu Tanrıverdi; Burcu Ataçer (Research on Ageing and Social Policy)
This study examines the relationship between perceptions and attitudes towards the COVID-19 pandemic and perceptions of aging and old age among academicians aged 65 and above. The sample consists of academics aged 65 and over from all universities in Turkey (208 universities). The study was completed with feedback from 187 participating academics.Data were collected through an online survey using a Google Form. The survey included a demographic questionnaire and scales to assess perceptions of COVID-19 and attitudes towards aging and old age. Ethical approvals and informed consent were obtained from participants. Data analysis involved descriptive statistics and Pearson correlation using SPSS 25.0 software. The findings reveal that approximately half of the senior academics had chronic illnesses, and about one-third had contracted COVID-19. More than half of the participants reported negative impacts of pandemic restrictions, disruptions in academic activities, and discomfort with the association of chronological age with old age. Statistical analysis demonstrates a significant positive relationship between perceptions and attitudes towards COVID-19 and perceptions of aging among elderly academics (p<0.05). This study highlights the interconnectedness of resistance to aging, avoidance behaviors, and positive attitudes towards COVID-19 among elderly academicians. These results suggest that perceptions of aging and attitudes towards the pandemic are intertwined in this population.